When Rights Are Forgotten: The Loss of Iddah and Mut'ah Maintenance in Default Divorce Decisions - Musfira Rahmi (al-Afkar, Journal For Islamic Studies, 2025)
The neglect of the fulfillment of iddah and mut’ah maintenance in divorce decisions made by default remains a serious problem in the practice of religious courts in Indonesia. This article examines this issue through a case study of Decision No. 156/Pdt.G/2018/PA.Lbs as a representation of the tendency of judges to prioritize a formal-procedural approach over the protection of the wife’s substantive rights. This research uses a normative juridical approach and case study, and aims to answer two main questions: whether the Respondent’s absence can be a legal reason to eliminate the right to iddah and mut’ah maintenance, and what is the basis for the judge’s consideration in not including these obligations in the decision. The results of the study indicate that the wife’s absence does not automatically revoke her rights, as long as there is no evidence of nusyuz or other legal conditions that cancel these rights. The judge’s decision, which is solely based on formal procedures without considering the principles of substantive justice and the protection of women, is contrary to the provisions of the Compilation of Islamic Law, Law No. 1 of 1974, and PERMA No. 3 of 2017. Therefore, it is necessary for the judge to implement ex officio authority to ensure that women's economic rights are fulfilled in divorce, even if the case is decided by default.